Seed Yield of Promising Pasture Forage Plant Species - A. S., Bobaeva (American Journal of Bioscience and Clinical Integrity, 2025)
General Background: Natural pastures serve as vital ecosystems that support livestock and contribute to sustainable agriculture. However, the declining productivity of pastures due to overgrazing, climate change, and soil degradation necessitates the development of effective restoration strategies. Specific Background: One of the key methods for improving pasture productivity is the establishment of primary seedbeds of promising pasture plant species, which ensures high-quality seed availability and enhances forage growth. Knowledge Gap: Although various pasture improvement techniques exist, limited research has been conducted on the effectiveness of primary seedbeds in ensuring long-term pasture sustainability. Aims: This study aims to examine the role and significance of primary seedbed establishment in increasing the productivity of natural pastures. Results: The findings highlight that primary seedbeds contribute to improved plant establishment, increased biomass yield, and enhanced soil fertility. Additionally, selecting appropriate species adapted to local climatic conditions plays a crucial role in sustaining pasture ecosystems. Novelty: This research provides a comprehensive analysis of how targeted seedbed development can optimize pasture restoration efforts and ensure sustainable grazing management. Implications: The study underscores the necessity of integrating primary seedbed development into pasture management policies to enhance forage quality, support biodiversity, and improve livestock production.